(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Delay Obligation Debt Payment or furthermore called PKPU is one of them possible efforts taken by the debtor For avoid bankruptcy. Basically, mean from granting PKPU to debtor is so that si existing debtors in circumstances insolvent, having chance for submit something plan peace, fine form offer For debt repayment whole or part on the debt. Therefore, that is, delay obligation debt repayment is chance for is debtor For pay off or carry out his obligations on these debts, so debtor the No until stated bankruptcy.